User Generated Content and Source Credibility Influence on Restaurant Consumer Decision Making - Chintia Romadayanti; Heri Setiawan; Kiki Azakia (Penerbit Goodwood, 2026)
Purpose: This study examines the influence of User Generated Content (UGC) and source credibility on consumer decision making in restaurant selection, focusing on consumers in Palembang City. It aims to understand how user created online content and perceived credibility shape consumer preferences and purchase behavior. Methodology/approach: A quantitative survey in Palembang was conducted involving 204 respondents who had previously used social media or online platforms before choosing a restaurant. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among the variables. Results/findings: The findings show that UGC has a significant positive impact on consumer decisions both directly and indirectly. UGC also enhances perceptions of source credibility, which in turn significantly affects decision making. Furthermore, source credibility partially mediates the relationship between UGC and consumer decisions. Text-based reviews were found to be more influential than visual content, suggesting the presence of demographic and cultural differences among respondents. Conclutions: The results confirm that credible and authentic UGC plays a crucial role in influencing restaurant choice behavior. Consumers are not only influenced by content availability but also by its trustworthiness and relevance. Limitations: The purposive sampling focused on young female respondents, limiting generalizability. The removal of some indicators highlights the need for refined measurement tools, particularly for visual media. Contribution: This study expands consumer behavior theory and provides practical insights for restaurant managers to strengthen digital trust and engagement.